Long‐term outcomes of Holmium laser enucleation of prostate and predictive model for symptom recurrence. Issue 2 (25th October 2021) - Droghetti, Matteo; Porreca, Angelo; Bianchi, Lorenzo; Piazza, Pietro; Giampaoli, Marco; Casablanca, Carlo; D'Agostino, Daniele; Cochetti, Giovanni; Romagnoli, Daniele; Schiavina, Riccardo; Brunocilla, Eugenio
Abstract: Introduction and objectives: Holmium laser enucleation of prostate (HoLEP) represents one of the most studied surgical techniques for benign prostatic hyperplasia (BPH). Its efficacy in symptom relief has been widely depicted. However, few evidence is available regarding the possible predictors of symptom recurrence. We aimed to evaluate long‐term outcomes, symptom recurrence rate, and predictors in patients that underwent HoLEP. Materials and Methods: We retrospectively analyzed data from patients that consecutively underwent HoLEP for BPH from 2012 to 2015 at two tertiary referral centers. Functional outcomes were evaluated by uroflowmetry parameters and International Prostate Symptom Score (IPSS) questionnaire administration at follow‐up visits at 12, 24, and 60 months. The primary outcome was the symptomatic patients' rate presenting lower urinary tract symptoms (LUTS) after 60 months from surgery, defined as in case of one or more of the following: IPSS more than 7, post voidal residue (PVR) more than 20 ml, need for medical therapy for LUTS or redo surgery for bladder outlet obstruction. Multivariable logistic regression analyses evaluated predictors for being symptomatic at follow‐up. Covariates consisted of: preoperative peak flow rate (PFR), PVR, and IPSS, prostate volume, age (all as continuous), and surgical technique. Results: A total of 567 patients were available for our analyses. Median prostate volume was 80cc, with a median PFR of 8 ml/s and median PVR of 100cc. One hundred and twenty‐five (22%) patients were found to be symptomatic at follow‐up. Redo surgery was needed for 25 (4.4%) patients. After adjusting for possible confounders, an increase in preoperative PVR (odds ratio [OR] 1.005) and IPSS (OR 1.12) resulted as independent predictors for symptom recurrence (all p < 0.001). Conclusions: HoLEP can provide durable symptom relief regardless of the chosen technique. Patients with an important preoperative symptom burden or a high PVR should be carefully counseled on the risk of symptom recurrence.